Zonal adult Hirschsprung's disease. Issue 5 (November 1996) - Fu, C G; Muto, T; Masaki, T; Nagawa, H
Abstract : BACKGROUND: Hirschsprung's disease is a congenital disorder which is rare in adulthood. In typical cases the aganglionosis involves mainly the rectum or rectosigmoid colon and the lesion starts from the anal valve. Zonal segmental aganglionosis is a very rare type even in children. PATIENT: A 54 year old women with zonal segmental aganglionosis had an aganglionic segment 18 cm in length located in the rectosigmoid colon with an 8 cm long normal appearing rectum and dilated proximal colon. Resection of the stenotic segment with end to end anastomosis was performed. CONCLUSION: The functional result was excellent five years after the operation.